COLD SNARE POLYPECTOMY: A SAFE PROCEDURE FOR REMOVING SMALL NON-PEDUNCULATED COLORECTAL LESIONS - Carlos Eduardo Oliveira Dos SANTOS; Daniele MALAMAN; Ivan David Arciniegas SANMARTIN; Ari Ben-Hur Stefani LEÃO; Isadora Zanotelli BOMBASSARO; Júlio Carlos PEREIRA-LIMA (Arquivos de Gastroenterologia, 2023)
ABSTRACT Background: Polypectomy is an important treatment option for preventing colorectal cancer. Incomplete polyp resection (IPR) is recognized as a risk factor for interval cancer. Objective: The primary objective was to evaluate the complete polyp resection (CPR) rate for cold snare polypectomy (CSP) in small non-pedunculated polyps and, secondarily, specimen retrieval and complication rates. Methods: We prospectively evaluated 479 polyps <10 mm removed by CSP in 276 patients by an inexperienced endoscopist. Results: A total of 476 polyps (99.4%) were resected en bloc. A negative margin (classified as CPR) was observed in 435 polyps (90.8%). An unclear or positive margin (classified as IPR) was observed in 43 cases (9.0%) and 1 case (0.2%), respectively, for an overall IPR rate of 9.2% (44/479). The IPR rate was 12.2% in the first half of cases and 5.9% in the second half (P=0.02). Dividing into tertiles, the IPR rate was 15.0% in the first tertile, 6.9% in the second tertile, and 5.7% in the third tertile (P=0.01). Dividing into quartiles, the IPR rate was 15.8% in the first quartile and 5.9% in the fourth quartile (P=0.03). The IPR rate was 6.3% for type 0-IIa lesions and 14.1% for type 0-Is lesions (P=0.01). For serrated and adenomatous lesions, the IPR rate was 9.2%. Specimen retrieval failed in 3.6% of cases. Immediate bleeding (>30 s) occurred in 1 case (0.2%), treated with argon plasma coagulation. No delayed bleeding or perforation occurred. Conclusion: CSP is a safe technique that provides good results for the resection of small non-pedunculated polyps, with a short learning curve.